State-of-the-art developments and perspectives on multifunctional magnetic soft composites (MMSCs) - Ahmad Shahir, Jamaludin; Nurul Najwa, Ruzlan; Mohd Zairulnizam, Mohd Zawawi; Ahmad Rosli, Abdul Manaf; Roshaliza, Hamidon (Springer, 2024)
The field of material science and engineering has seen a growing interest in Multifunctional Magnetic Soft Composites (MMSCs) due to their unique magnetic properties, flexibility, and diverse range of functionalities. These composite materials, which possess magnetic responsiveness and adaptability, have been utilized in various fields such as soft robotics and biomedical advancements. Significantly, the incorporation of MMSCs into soft robotic systems has facilitated the ability to navigate complex environments and perform precise object manipulation, thereby surpassing the capabilities exhibited by conventional rigid robots. Moreover, MMSCs have demonstrated potential in various biomedical applications, such as drug delivery systems, medical textiles, and targeted therapies. The progress in fabrication techniques, such as 3D printing, and the integration of novel insulating layers have significantly advanced research on MMSCs, leading to improvements in their characteristics and expanding their range of potential applications. Nevertheless, notwithstanding these notable progressions, there exist certain lacunae in the research, specifically pertaining to the comprehension of time-dependent electric conductivity of MMSCs in high-electric fields and the investigation of symmetry-breaking actuation mechanisms. By addressing these knowledge deficiencies and effectively utilizing the untapped potential of MMSCs in unexplored areas such as high-voltage systems and diverse biomedical applications, there is a possibility of significantly transforming their influence in multiple sectors. Future research endeavors should give priority to these areas, in order to ensure the ongoing evolution of MMSCs and their crucial role in shaping technological advancements.